Two methods of drying eucalyptus wood after impregnation with silver nanoparticles - Valcorte, Guilherme; Roubuste, Roberta Rodrigues; Baldin, Talita; Souza, Kássya Melissa Oliveira de; Oliveira, Laura Hoffman de; Santini, Elio José (Scientia Agraria Paranaensis, 2023)
In view of its importance in the forestry industry and the commercialization of wood, there is a clear need to implement technologies that provide better quality wood and improved drying processes. Therefore, this study aimed to evaluate two methods of drying Eucalyptus grandis W. Hill wood after impregnation with silver nanoparticles. For this purpose, logs of this species were used, which, after making the specimens and impregnating silver nanoparticles at concentrations of 40 and 100 mg L-1, were subjected to drying in an air-conditioned chamber with an average temperature of 20°C and relative humidity of 65% and a laboratory oven with forced circulation at a constant temperature of 60°C, for subsequent analysis of moisture content, drying rate, and defects. The results showed a greater loss of moisture in the pieces impregnated with 40 mg L-1, dried in an oven and air-conditioned chamber, and a higher drying rate in the oven. In addition, there was a higher incidence of defects in wood impregnated with 100 mg L-1 and dried in an oven. The specific mass obtained average values similar to those referenced in the literature for this species. Based on the results of this study, it was possible to conclude that the impregnation of Ag NP’s brings benefits in terms of the drying rate, allowing for a greater loss of moisture from the wood. In addition, the treatment reduces warping defects. These effects are found mainly in wood impregnated with 100 mg L-1.